PENGARUH HOLDING TIME DAN MOLD TEMPERATURE TERHADAP CACAT WARPAGE PADA PROSES KOMPOSIT AL-PP DENGAN INJECTION MOLDING - khoirul fahmi aziz; Aris Zainul Muttaqin; Intan Hardiatama; Hari Arbiantara; Sumarji .; Dwi Djumhariyanto (STATOR: Jurnal Ilmiah Teknik Mesin, 2022)
Success in the injection molding process is seen from the results of products that do not produce defects. Warpage defects are one of the defects resulting from the injection molding process. One way to measure warpage defects is to use the ImageJ application. The data processing stage in this study uses the Taguchi method statistical method with two independent variables namely holding time and mold temperature, each of which has three factors and repeated data three times, which aims to obtain more accurate values. The results showed a very influential variable is the holding time parameter then the mold temperature parameter. The higher the level of holding time parameters, the smaller the result of warpage defects. Unlike the holding time parameters, the best mold temperature parameters at the middle level, the result will be a small warpage defect produced. The experimental results of the highest level value on the holding time parameter are 15 seconds while in the mold temperature the value of the middle level is 50 ° C which produces a defect of 1%. While the lowest holding time parameter value is 5 seconds and the highest mold temperature level parameter value of 70 ° C is the worst variation of parameters because it produces a defect of 22%.